Misclassification probability as obese or lean in hypercaloric and normocaloric diet - Nascimento, Andre F. [UNESP]; Sugizaki, Mario M. [UNESP]; Leopoldo, Andre S. [UNESP]; Lima-Leopoldo, Ana P. [UNESP]; Nogueira, Célia Regina [UNESP]; Novelli, Ethel L. B. [UNESP]; Padovani, Carlos Roberto [UNESP]; Cicogna, Antonio Carlos [UNESP] (Soc Biolgia Chile, 2008)
The aim of the present study was to determine the classification error probabilities, as lean or obese, in hypercaloric diet-induced obesity, which depends on the variable used to characterize animal obesity. In addition, the misclassification probabilities in animals submitted to normocaloric diet were also evaluated. Male Wistar rats were randomly distributed into two groups: normal diet (ND; n=3 1; 3,5 Kcal/g) and hypercaloric diet (HD; n=31; 4,6 Kcal/g). The ND group received commercial Labina rat feed and HD animals a cycle of five hypercaloric diets for a 14-week period. The variables analysed were body weight, body composition, body weight to length ratio, Lee index, body mass index and misclassification probability A 5% significance level was used. The hypercaloric pellet-diet cycle promoted increase of body weight, carcass fat, body weight to length ratio and Lee index. The total misclassification probabilities ranged from 19.21 % to 40.91 %. In Conclusion, the results of this experiment show that rnisclassification probabilities Occur when dietary manipulation is used to promote obesity in animals. This misjudgement ranges from 19.49% to 40.52% in hypercaloric diet and 18.94% to 41.30% in normocaloric diet.
Keywords: Diet; diet-induced obesity; hypercaloric diet; misclassification; rats